Injury risk factors to farm and ranch operators in the Central United States. Issue 10 (28th August 2017) - Jadhav, Rohan; Achutan, Chandran; Haynatzki, Gleb; Rajaram, Shireen; Rautiainen, Risto
Abstract : Background: This study focused on risk factors for serious injuries in farm and ranch operators in the central United States. Methods: The Central States Center for Agricultural Safety and Health, in collaboration with the National Agricultural Statistics Service, sent mail surveys to 6953, 6912, and 6912 farms/ranches in 2011‐2013, respectively, covering seven Midwestern states. Results: The average survey response rate was 35%. The average annual incidence rate (injuries/100 workers) was 6.91 for all injuries and 2.40 for serious injuries. Univariate analyses determined several demographic and farm production‐related risk factors for serious injury. Adjusted analysis showed a greater risk of serious injury for operators of age 45‐54 years (vs. 65 and higher), those who worked 75‐99% of their time (vs. less time), and those who operated larger land areas (vs. smaller). Conclusion: The identified risk factors should be considered when targeting injury prevention programs.